The The Utilization of Spirit of Saemaul Undong through Village Renewal Program in DI Yogyakarta - Shannaz Deniar; Juwita Maharani (Jurnal Partisipatoris, 2022)
Saemaul Undong is a sustainable development concept which already applied in several developing countries as well as in Indonesia. Saemaul Undong which means the new village movements aims to improve the village area that is experiencing inequality with the urban area. Saemaul Undong has 3 principles of spirit, namely diligence, self-help, and cooperation, with this principle of three spirits, the villagers are able to advance their village. Because of this successful, Saemaul Undong expanded into the global realm and became the Memory of World Register which was inaugurated by UNESCO. This research discusses the application of the three Saemaul Undong spirits through village renewal policy programs in Yogyakarta. This research uses the concept of the three Saemaul Undong spirits to explain the interrelationship between the village renewal programs implemented in the three villages that are used as pilot projects for Saemaul Undong. This research uses qualitative methods with data collection techniques through fieldwork, literature study, and literature review. Data were obtained from various sources such as interviews with resource persons, books, journals, theses, articles, or news and official websites related to Saemaul Undong.